Surface-tailored graphene nanosheets targeting PI3K/Akt signaling of breast cancer cells - Sabapathi Durgadevi; Ponnuchamy Kumar (Scientific Reports)
Abstract Herein, we report graphene nanosheets fabricated using liquid-phase exfoliation of graphite employing cetyltrimethylammonium chloride (CTAC) in an aqueous medium. The salient features of CTAC-assisted graphene nanosheets are as follows: (i) the concentration of graphene dispersed in water is found to be 26.01 mg/mL at 50 mg with a Critical Micelle Concentration (CMC) Value of 3 mg/mL (9.375 mM); (ii) rapid exfoliation is assisted by CTAC via sonication, which develops hydrophilic micelles on graphitic surface; (iii) the strong repulsive force of CTAC prevents re-aggregation of graphene sheets by means of electrostatic interaction as revealed by zeta potential measurement (+ 33.8 mV); (iv) the graphene nanosheets display excellent anticancer properties against MCF-7 (IC50 – 205.5 ng/mL) and MDA-MB-231 (IC50 – 216.9 ng/mL) breast cancer cells; (v) the CTAC assisted graphene nanosheets induce PI3K/Akt mediated apoptosis in breast cancer cells. Based on the results, CTAC-assisted graphene nanosheets are expected to be a potential candidate for therapeutic applications in the near future.